Health and Relaxation Corner: Empowering Food Vendors Around Hospitals Through Innovative Training - Frengki Apryanto; Rahmaniah Ramadhani; Rudy Joegijantoro (STIKes Patria Husada Blitar, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in the culinary sector play a vital role in supporting the economy, particularly around hospitals where food demand is consistent. However, many vendors face challenges such as poor hygiene practices, limited menu innovation, inadequate financial literacy, and lack of consumer-friendly facilities, which reduce competitiveness and pose risks to public health. To address these issues, the Healthy & Relaxing Corner community service program was implemented with 20 vendors from 10 stalls around Saiful Anwar Hospital, Malang, through outreach, training, mentoring, provision of simple technologies, and participatory evaluation. The training modules included Clean and Healthy Living Behavior; PHBS (Perilaku Hidup Bersih dan Sehat), food safety, herbal menu diversification, financial management, product photography, digital marketing, waste management, and stall layout improvements. The results demonstrated significant progress: knowledge improved from 65% poor to 90% good, PPE use rose from 25% to 100%, and all participants achieved proper financial recording skills. Additionally, 75% reached good practice in product photography, 50% attained good ability in digital promotion, and 100% adopted correct waste sorting. All stalls successfully introduced herbal drinks, while half modified cooking techniques for healthier food preparation. However, only 30% of vendors created relaxing corners, suggesting that financial and space constraints limited physical restructuring. Overall, the program effectively improved hygiene, entrepreneurship, and innovation, contributing to healthier food environments and more sustainable income for vendors. The model is replicable for MSME empowerment in other communities, with future initiatives recommended to combine training with micro-financing or infrastructure support to maximize outcomes.